Le Comédien - Remond de Sainte-Albine, Pierre 1699-1778; Gravelot, Hubert-François 1699-1773 (Paris Desaint & Saillant Vincent, 1747)
'Le Céomdien' is comprehensive work designed to lay down the principles of the profession for novice actors. The author's intention was, "while awaiting the publication of a treatise on the Art of Acting such as one would be entitled to desire, to help those who wish to embrace this Profession to know whether they are suitable for the Theatre, and to discover some of the means by which they can hope to win applause there". The author ends his speech with a declaration in favour of recognising young talent, and against "the sad folly of the admirers of the past". This treatise provoked Diderot's 'Paradoxe du comédien' (1770-8).
Frontispiece designed by Gravelot, with the motto “Facies mutat semperque decenter.”
Ex Libris Jean Armand Tronchin (Plate)
Keywords: Diderot, Denis -- 1713-1784; 18th Century (1701-1800); Theater history; Acting; Method; France